Molecular Methods for Diagnosis of Infective Endocarditis - Moter, Annette (2002)
Infective endocarditis (IE) is a life-threatening disease associated with high mortality. Conventional microbiologic diagnosis is based mainly on culture-dependent methods that often fail because of previous antibiotic therapy or the involvement of fastidious or slowly growing microorganisms. In recent years, molecular techniques entered the field of routine diagnostics. Amplification-based methods proved useful for detection of microorganisms in heart valve tissue. More recently, they were applied to blood samples from patients with IE. Direct detection of microorganisms in valve specimens by fluorescence in situ hybridization allowed identification of the causative agent and simultaneous visualization of complex microbial communities. These techniques will gain more importance in the near future, provided that procedures are standardized and results are interpreted with caution. With this review, we intend to give an overview of the impact and limitations of molecular techniques for the diagnosis of IE, including a focus on recent developments.